Fluxes of carbon dioxide gases (CO2) in the mangrove soil of Passo Village, Ambon City - Rahman, Rahman; Ratuluhain, Eva Susan; Fakaubun, Fahrul Rozy; Soukotta, Imanuel Villian Trayanta (Politeknik Negeri Sambas, 2024)
Mangrove ecosystems play a significant role in carbon absorption. However, the accumulation of organic matter in mangrove sediments undergoes decomposition, which triggers the release of CO2 gas flux. This study aimed to analyze the CO2 gas flux in mangrove sediments of Negeri Passo, Ambon City. Gas data collection was performed using cylinder canopies at the three observation stations. Gas was passed through the syringe five times with an interval of 30s. Gas concentration analysis was carried out using the gas chromatography method, while CO2 flux was analyzed with flux equations referring to slope regression, volume and area of the scope, temperature, molecular weight of the gas, ideal gas settings, and time constants based on gas intake intervals. The results showed that the average CO2 concentration in St. 1 was 465.14 ± 96.52 ppm, and was the lowest compared to St. 2 and St. 3 with values of 638.60 ± 90.05 ppm and 630.98 ± 54.09 ppm, respectively. Meanwhile, the average CO2 flux was 50.44 mg/m2/hour. The largest CO2 gas flux was observed at St. 2 at 103.69 mg/m2/hour. Meanwhile, the lowest flux was found at St. 3, which was 16.24 mg/m2/hour. Based on this, it can be concluded that] the mangrove ecosystem in Negeri Passo has a higher concentration of CO2 gas than the average concentration of climate change stabilization scenarios. However, the CO2 flux was lower than that at other locations in the Ambon Dalam Bay area. In addition, the potential for significant carbon sequestration based on the Tier 1 model approach indicated that mangrove ecosystems in this location play an important role in climate change mitigation.